Strategi Pengembangan Usaha Melalui Digital Marketing Pada Kebun Hidroponik Hiroto Farm Bogor - Henita Fajar Oktavia; Safira Fathin; Nayla Noorvita (Agrisia: Jurnal Ilmu-Ilmu Pertanian, 2022)
Indonesia is known as an "Agrarian Country" due to its significant agricultural potential. One of the developing agricultural systems in Indonesia is hydroponics. Hiroto Farm is a hydroponic farming company located in Bogor City. It focuses on the B2B (Business-to-Business) market and targets restaurants and supermarkets in Bogor, Jakarta, and Tangerang. However, to date, Hiroto Farm's products have not been optimally absorbed by the market. The purpose of this research was to formulate business development ideas using a SWOT analysis of Hiroto Farm in Bogor City and to develop a business development plan through digital marketing. The conclusion obtained was that through the SWOT analysis of Hiroto Farm, a business development idea was derived: expanding the hydroponic vegetable market through digital marketing. This business idea is a solution to reduce losses from excess production volume by capitalizing on opportunities arising from shifts in healthy food consumption patterns and the increasing online purchasing patterns of consumers. This business idea will target a new market, namely end consumers, thereby increasing Hiroto Farm's sales. Therefore, Hiroto Farm needs to keep abreast of technological developments and the latest information regarding online businesses. Companies need to be selective in recruiting workers who will later manage digital marketing because digital marketing requires precision in analyzing existing trends in society so that companies will be able to create appropriate marketing strategies that are in accordance with company conditions and appropriate marketing to target consumers.